The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4141/cjps2013-402
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing inputs for winter durum wheat in Ontario

Abstract: . 2015. Optimizing inputs for winter durum wheat in Ontario. Can. J. Plant Sci. 95: 361Á368. Best management practices need to be determined for a new wheat class in Ontario: winter durum. The objectives of this study were to determine optimal nitrogen rates (75, 100, and 125 . Grain yields did not increase with N rates higher than 100 kg N ha(1 , and the response to N rate did not depend on the application of fungicides. Grain protein concentrations increased with N rates up to 125 kg N ha(1 , which was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In a similar way, Kilic and Gursoy (2010) found that 253 seeds m –2 had the greatest yield when studying a range from 50 to 550 seeds m –2 . Tamburic‐Ilincic et al (2015) observed no effect of greater seeding rates, although the range was narrow, from 400 to 480 seeds m –2 , which is a rather dense seeding rate, and was with winter durum. Conversely, Arduini et al (2006) and Isidro‐Sánchez et al (2017) observed increased yield with increasing seeding rate, the latter spanning a 2.3× rate.…”
mentioning
confidence: 95%
“…In a similar way, Kilic and Gursoy (2010) found that 253 seeds m –2 had the greatest yield when studying a range from 50 to 550 seeds m –2 . Tamburic‐Ilincic et al (2015) observed no effect of greater seeding rates, although the range was narrow, from 400 to 480 seeds m –2 , which is a rather dense seeding rate, and was with winter durum. Conversely, Arduini et al (2006) and Isidro‐Sánchez et al (2017) observed increased yield with increasing seeding rate, the latter spanning a 2.3× rate.…”
mentioning
confidence: 95%